Acute and chronic effects of erythromycin exposure on oxidative stress and genotoxicity parameters of Oncorhynchus mykiss - Rodrigues, S. (2022)
Erythromycin (ERY) is a macrolide antibiotic used in human and veterinary medicine, and has been detected in various aquatic compartments. Recent studies have indicated that this compound can exert biological activity on non-target organisms environmentally exposed. The present study aimed to assess the toxic effects of ERY in Oncorhynchus mykiss after acute and chronic exposures. The here adopted strategy involved exposure to three levels of ERY, the first being similar to concentrations reported to occur in the wild, thus ecologically relevant. Catalase (CAT), total glutathione peroxidase (GPx), glutathione reductase (GRed) activities and lipid peroxidation (TBARS levels) were quantified as oxidative stress biomarkers in gills and liver. Genotoxic endpoints, reflecting different types of genetic damage in blood cells, were also determined, by performing analysis of genetic damage (determination of the genetic damage index, GDI, measured by comet assay) and of erythrocytic nuclear abnormalities (ENAs). The results suggest the occurrence of a mild, but significant, oxidative stress scenario in gills. For acutely exposed organisms, significant alterations were observed in CAT and GRed activities, and also in TBARS levels, which however are modifications with uncertain biological interpretation, despite indicating involvement of an oxidative effect and response. After chronic exposure, a significant decrease of CAT activity, increase of GPx activity and TBARS levels in gills was noticed. In liver, significant decrease in TBARS levels were observed in both exposures. Comet and ENAs assays indicated significant increases on genotoxic damage of O. mykiss, after erythromycin exposures. This set of data (acute and chronic) suggests that erythromycin has the potential to induce DNA strand breaks in blood cells, and demonstrate the induction of chromosome breakage and/or segregational abnormalities. Overall results indicate that both DNA damaging effects induced by erythromycin may be related to the oxidative damage observed, shown to occur at environmentally relevant concentrations of erythromycin.